2021
DOI: 10.1098/rsos.201204
|View full text |Cite
|
Sign up to set email alerts
|

The search for a sustainable alternative to slash-and-burn agriculture in the World's rain forests: the Guama Model and its implementation

Abstract: This account describes the context, history and outcomes of a series of studies into the ecology of slash-and-burn (S-B) agriculture in the world's humid tropics. These studies, which began in the mid-1980s, identified promising lines of research and continued to field trials, in Central America, of candidate agricultural systems as possible sustainable alternatives to the practice. The only system to emerge from 7 years' comparative trial with any promise of sustainability, in this context, was the agroforest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Consistent with the findings of previous studies [ 40 ], soils showed a trend of acidification after multi-generational succession, but soil OM and TN were significantly elevated in sprouted second-generation stands, but fast-acting nutrient elements generally showed a decreasing trend. The soil was exposed due to violent soil disturbance (slash and burn) during the new plantation process, which destroyed the soil structure and caused a large loss of SOM and nutrient elements in the T0 and T1 stands [ 41 , 42 ]. After mature felling of newly planted forests, the sprouting and re-growth operation was adopted, which does not require clearing of harvesting residues, so nutrients were gradually accumulated within the soils of second- and third-generation stands [ 43 ], while the accumulation of nutrient elements is also promoted by heavy fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of previous studies [ 40 ], soils showed a trend of acidification after multi-generational succession, but soil OM and TN were significantly elevated in sprouted second-generation stands, but fast-acting nutrient elements generally showed a decreasing trend. The soil was exposed due to violent soil disturbance (slash and burn) during the new plantation process, which destroyed the soil structure and caused a large loss of SOM and nutrient elements in the T0 and T1 stands [ 41 , 42 ]. After mature felling of newly planted forests, the sprouting and re-growth operation was adopted, which does not require clearing of harvesting residues, so nutrients were gradually accumulated within the soils of second- and third-generation stands [ 43 ], while the accumulation of nutrient elements is also promoted by heavy fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…spp.) en la región del bosque húmedo del país; sobre todo, en el Departamento de Atlántida (Hands, 2021). Este cultivo permite la recuperación de terrenos al fijar grandes cantidades de nitrógeno (N 2 ), generar hojarasca que evita la proliferación de malezas y evitar la erosión; además, sirve de sombra intermedia en sistemas agroforestales con cacao (eobroma cacao) y/o café (Coffea arabica), y es clave para mejorar la seguridad alimentaria de la población, ya que su fruto es comestible.…”
Section: Honduras Y Los Senderos Productivos De La Bioeconomía Valoración De Los Recursos De Base Biológicaunclassified
“…This combination of plants brings about an equilibrium in the productive system favouring food security, strengthening resilience of socio-ecological systems and carbon fixing as a strategy to mitigate climate change (Colon-García, 2021). On the other hand, the Guama Model, is an agricultural production system in alleys, using Inga trees, this system is an option for achieving sustainable rural development in the humid tropics (Hands, 2021) because it increases water storage in the soil, improves soil fertility, increases cation exchange capacity (CEC) of the soil, decreases soil temperature due to litter accumulation on the surface and blocks the growth of weeds. Even though these systems offer advantages, they require external fertilization, such as in maize (Catari-Yujra et al, 2022), coffee (Sanchez, 2017), and cacao (López, 2015).…”
Section: Introductionmentioning
confidence: 99%